Natural convection in T-shaped cavities filled with water-based suspensions of COOH-functionalized multi walled carbon nanotubes. (February 2017) - Esfe, Mohammad Hemmat; Arani, Ali Akbar Abbasian; Yan, Wei-Mon; Aghaei, Alireza
Abstract: In the present study, natural convection fluid flow and heat transfer inside a T-shaped cavity filled with water-based suspensions of COOH-functionalized multi walled carbon nanotube has been numerically investigated. The considered cavity is a T-shaped enclosure having six walls at high constant temperature (Th ) and a horizontal top wall at low temperature (Tc ) while the bottom wall is kept thermally insulated. To carry out the numerical simulations, the governing equations are discretized employing the finite volume method (FVM) while the SIMPLER algorithm is used to couple velocity and pressure fields to solve governing mass, momentum, and energy equations. The effects of solid volume fraction from 0.0% to 1.0%, the aspect ratio between 0.2 and 0.8 of the T-shaped cavity and Rayleigh number range of 10 3 and 10 5 on the fluid flow and heat transfer inside the cavity are examined in details. According to the predicted results, the average Nusselt number increases (to 124%) with increase in the solid volume fraction of nanofluid and Rayleigh number for different aspect ratios. Also, at low Rayleigh number, Ra=10 3 or 10 4, the conduction dominates the transport phenomenon in the T-shaped cavity. Therefore, the average Nusselt number decreases with an increase in aspect ratio. Highlights: Natural convection inside a T-shaped cavity filled with nanofluids has been investigated. The effects of solid volume fraction, the aspect ratio and Rayleigh number on the fluid flow and heat transfer are presented. Average Nusselt number increases with increase in the solid volume fraction and Rayleigh number for different aspect ratios.